A critical COVID-19 patient managed with timely evaluation, early prone positioning ventilation, and a multi-pronged pharmacotherapy. (June 2021) - Peng, Mian; Li, Rongsong; Cao, Weiling; Li, Weiqing; Wu, Ming; Lyu, Yansi; Meng, Xi; Ji, Kunmei
There is not yet a standard drug regimen for the treatment of coronavirus disease 2019 (COVID-19) patients. Here, we summarize our experience and successful treatment plan with a critical COVID-19 patient who required mechanical ventilation (MV). A 56-year-old man presented with a fever, cough, and dyspnea. He had not been to a medium/high risk epidemic area in the past year and had no family history of a disease cluster. COVID-19 was suspected based on clinical symptoms and radiologically detected ground-glass lung changes in the context of a normal white blood cell count (WBCC) and lymphocyte fraction (L%). A diagnosis of COVID-19 was confirmed by nucleic acid testing. Initially, he was started on noninvasive ventilation (NIV). Because his respiratory distress worsened over the following 2 h, he was transitioned to mechanical ventilation (MV), placed in prone positioning 12 h/day, and given a multi-pronged pharmacotherapy regimen that included an antiviral cocktail (lopinavir/ritonavir plus α-interferon), an immunity enhancer (thymosin α1), an anti-coagulant to prevent thrombosis (heparin). He was given an antibiotic to treat an opportunistic nosocomial infection. The patient has recovered well. The regimen applied in this case of timely evaluation, early prone positioning with MV, and a multi-pronged pharmacotherapy may be an effective strategy for patients with critical COVID-19, particularly with respect to preventing life-threatening worsening of the illness.